Study of Conversion of Bio-oil Model Compounds in Supercritical Water Using Density Functional Theory - Agrawal, Kushagra (Sci Rep, 2020)
It is well known that supercritical water is a favourable medium for biomass conversion followed by its hydrodeoxygenation (HDO). Moreover, the actual kinetics and mechanism of reaction occurring in the supercritical water are not yet completely understood, either by experimental or computational approaches. Within the framework of DFT, the major challenge is non-availability of models to simulate supercritical phase. In this study, the authors manually define the descriptors of a solvation model to describe an implicit supercritical phase. In order to examine the suitability of supercritical water for thermal and hydrotreatment of bio-oil model compounds, nine different reactions involving conversion of furfural, tetrahydrofuran, xylose, phenol, guaiacol, ferulic acid, acetic acid, 2-hydroxybenzaldehyde and hydroxyacetone have been considered. Further these reactions are also studied in gas and liquid phase to compare results of different phases, including supercritical water. It was found that while HDO of aromatic compounds like phenol and 2-hydroxybenzaldehyde was favourable in the supercritical phase, smaller molecules like acetic acid and hydroxyacetone did not show much advantage in the supercritical phase over gas and liquid phase. It was also found that the thermochemical parameter - Gibbs free energy change (ΔG) was equally influenced by the solvation effect and the effect of temperature-pressure under supercritical conditions. In several instances, the two effects were found to offset each other in the supercritical phase.